MODEL OF ORGANIZATIONAL AND PEDAGOGICAL SUPPORT FOR THE DEVELOPMENT OF MEDICAL COLLEGE ACTIVITIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Research on the development of a medical college in modern socio-economic conditions is due to several circumstances. Among them, we can highlight the most acute problems that exist in the practice of modern healthcare, which need to be solved, including at the level of the medical college.